Seeking virtue in finance : contributing to society in a conflicted industry - De Swaan, J. C. (Jean-Christophe), 1971- (Cambridge : Cambridge University Press, 2020)
Since the Global Financial Crisis, a surge of interest in the use of finance as a tool to address social and economic problems suggests the potential for a generational shift in how the finance industry operates and is perceived. J. C. de Swaan seeks to channel the forces of well-intentioned finance professionals to improve finance from within and help restore its focus on serving society. Drawing from inspiring individuals in the field, de Swaan proposes a framework for pursuing a viable career in finance while benefiting society and upholding humanistic values. In doing so, he challenges traditional concepts of success in the industry. This will also engage readers outside of finance who are concerned about the industry's impact on society.
Customer mandate : serving customers' interest faithfully -- Social wealth creation : contributing to society beyond the customer mandate -- Humanistic leadership within the organization : treating colleagues with dignity, empowering them, and fostering a responsible culture -- Engaged citizenship : contributing expertise, time, and wealth to the common good.
Title from publisher's bibliographic system (viewed on 21 Sep 2020).
Keywords: Finance -- Moral and ethical aspects; Financial institutions -- Moral and ethical aspects; Financial services industry -- Employees -- Professional ethics; Social responsibility of business; Virtue